2021
DOI: 10.3390/su13116504
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity Effect of Calcium Carbonate on the Formation of Carboaluminate Phases in Ground Granulated Blast Furnace Slag Blended Cements

Abstract: The reactivity effect of calcium carbonate, present in ground oyster shells and limestone filler, on the formation of carboaluminate phases in ground granulated blast furnace slag blended cement pastes was reported in this paper. Six different binary and ternary blended cement pastes were prepared using ground granulated blast furnace slag, ground oyster shells and limestone filler with different replacement levels (from 5 to 35%). The carboaluminate formation was assessed and quantified directly using X-ray d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…This phenomenon demonstrated that calcium carbonate reacts and produces calcium carboaluminate hydrate products. The formation of carboaluminates has been observed in binary and ternary pastes with cement, ground BFS, limestone filler and ground oyster shells [ 23 ]. The authors of those research works established that calcium carbonate was consumed to form calcium hemi- and monocarboaluminate phases.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon demonstrated that calcium carbonate reacts and produces calcium carboaluminate hydrate products. The formation of carboaluminates has been observed in binary and ternary pastes with cement, ground BFS, limestone filler and ground oyster shells [ 23 ]. The authors of those research works established that calcium carbonate was consumed to form calcium hemi- and monocarboaluminate phases.…”
Section: Resultsmentioning
confidence: 99%
“…Calcite can react with aluminate phases in hydrating cement to form carboaluminate phases, among which mono- and hemicarboaluminate are the most common. This may result in an increase in comprehensive strength of cement [ 29 ]. However, if not all of the carbonate is used to form the carboaluminate it can be unstable, which will have a negative effect on the mechanical properties of the cement [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, substituting organic materials for fine aggregates can also have positive environmental implications. It can reduce the need for landfill sites for waste disposal and promote the efficient use of resources [29].…”
Section: Introductionmentioning
confidence: 99%